Analisis Struktur Omah Saka Papat di Blitar Terhadap Risiko Beban Gempa - Yoganata, Yehezkiel Septian; Fajarwati, Anisah Nur; Kurniawan, Achendri M.; Rahman, Aulia; Cahyani, Kharisma Nur (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Omah Saka Papat is a traditional Javanese architectural structure. It is characterized by four main wooden pillars (saka guru). These pillars reflect the structure's adaptability to environmental conditions. This includes earthquake risks. This study will analyze the structural strength of Omah Saka Papat under seismic and self-weight loads. The saka guru is a critical element of this analysis. STAAD Pro v8i software and the response spectrum method were used to calculate internal forces and evaluate the capacity of teak wood as the primary material. The findings indicate that the combined compressive stress of 123.34 kg/cm² and shear stress of 0.83 kg/cm² are both below the allowable limits of 150.75 kg/cm² and 20.1 kg/cm², respectively. Structural joints using 12.7 mm diameter bolts satisfy the required strength criteria, with a minimum of four bolts per joint. Omah Saka Papat's structural integrity is proven. It's an earthquake-resistant construction that preserves aesthetic and cultural values. Integrating traditional design principles with modern technology provides a sustainable construction model adaptable to natural disasters. These results will undoubtedly contribute to the development of locally inspired, earthquake-resistant construction technologies suitable for seismic-prone regions.